Hotels Environmental Certification Systems: Essence, Characteristics, Review - Jarosław PAWŁOWSKI (Communications of International Proceedings, 2022)
As a result of the development of tourism activity, the share of the hospitality industry in the global economy is important. Due to the nature of the activity hotels industry has a significant harmful impact on the environment. Observed growth of consumers' environmental awareness involved also hotels. It causes that environmental certification of hotels is getting more and more popular. Importance and topicality of that issues cause that this paper is focused on the problems of hotels environmental certification. The general data of the hospitality industry and harmful effects of the hotels on the environment will be presented first. Next, the pro-environmental behaviour in the hospitality sector and eco-certification of hotels. Finally, examples of hotels environmental certification systems and some conclusions about it. Methods which have been used: descriptive method, comparative method, reference books analysis and case study.
Keywords: hospitality industry; Pro-environmental behaviour; environmental certification